KNOWLEDGE AND USE OF EMERGENCY CONRACEPTION IN ADOLESCENCE: CONTRIBUTIONS FOR NURSING - Milena Freitas Rodrigues; Dulcilene Pereira Jardim (Universidade Federal do Paraná, 2012)
This descriptive-exploratory study aimed to identify the knowledge and use of emergency contraception among adolescents. Data collection was through a questionnaire responded to by 271 adolescents from a state school in São Paulo in 2010. The results show that 87.8% of the adolescents know the morning-after pill and how to use it, 28.8% had already used the morning-after pill, and the average use per adolescent was three times - and used correctly. Emergency contraception was not used by all the adolescents who had initiated sexual activity or who had sex or other sexual relations without protection, which represents a gap between knowledge and use of this form of contraception. It falls to the nurse, as an educator working in primary health care centers, schools and other social spaces, to develop strategies for reaching this population and contributing to its knowledge, to the prevention of unwanted pregnancy, and to the promotion of self-care.